Influence of drip irrigation on soil moisture content, water requirement and water use efficiency of peach (Prunus persica (L.) Batsch.) cv. Redhaven - VERMA, PRAMOD; CHANDEL, J. S. (Journal of Soil and Water Conservation, 2018)
A field experiment was conducted during the year 2015-2016 at Dr Y S Parmar University of Horticulture and Forestry, Solan, Himachal Pradesh, India, to study the comparative performance of drip irrigation and basin irrigation on soil moisture content, water requirement and water use efficiency of peach cv. Redhaven. The experiment was laid out in completely randomized block design with five treatments viz. drip irrigation at 100% ETc, 80% ETc, 60% ETc, basin irrigation at 100% ETc and rainfed (control) and each treatment were replicated five times. The results suggested that trees irrigated with drip irrigation at 100% ETc recorded highest average soil moisture content (23.09 and 23.25%, during 2015 and 2016, respectively), followed by trees irrigated with basin irrigation at 100% ETc, in comparison to other drip irrigation treatments and control. The total quantity of irrigation water applied per tree was maximum (76.35 and 96.64 cm during 2015 and 2016, respectively) in trees subjected to drip and basin irrigation at 100% ETc treatment in comparison to control and the highest total water requirement (93.23 and 108.78 cm/tree) was in trees subjected to basin irrigation at 100% ETc treatment in comparison to control. However, the maximum water-use-efficiency (0.15 and 0.20 Kg/tree/cm during 2015 and 2016, respectively) was found in trees irrigated with drip irrigation at 80% ETc and the minimum water-use-efficiency of 0.11 Kg/tree/cm was observed in control during the year 2015 and 0.14 Kg/tree/cm in trees irrigated with basin irrigation at 100% ETc.